Wahrscheinlichkeitstheorie: 18.3. bis 24.3.1973 - Bühler, Wolfgang J.; Waldenfels, Wilhelm von (Tagungsbericht, 1973)
L. Arnold, Bremen; P. Artzner, Straßburg; W. Bühler, Mainz; K. Daniel, Bern; M. Denker, Erlangen; H. Dinges, Frankfurt; U. Döring, Mainz; A. Dvoretzky, Jerusalem; G. K. Eagleson, Cambridge (UK); W. Eberl, Wien; E. Eberlein, Erlangen; H. Engmann, Bielefeld; H. Föllmer, Erlangen; P. Gänßler, Bochum; F. Hampel, Zürich; H. Hering, Berlin; H. Heyer, Tübingen; L. Jones, Göttingen; D. A. Kappos, Athen; M. Keane, Rennes; D. G. Kendall, Cambridge (UK); U. Krengel, Göttingen; K. Krickeberg, Paris; W. Krieger, Columbus (Ohio); P. A. Meyer, Straßburg; F. Papangelou, Göttingen; W. Philipp, Wien; P. Ressel, Freiburg; P. Révész, Budapest; J. Runnenburg, Amsterdam; C. L. Scheffer, Utrecht; M. Skolnick, Parma; M. Smorodinsky, Tel Aviv; M. Stoka, Bukarest; P. Tautu, Heidelberg; F. Topsøe, Kopenhagen; W. v. Waldenfels, Heidelberg; N. X. Xanh, Bielefeld; H. N. Zessin, Bielefeld